The dynamics of indigenous innovation in the Portuguese capital goods sector - Romero, Fernando (1998)
In this research work the analysis of the process of indigenous technological change in the equipment goods sector in Portugal is made. The framework of analysis is based on evolutionary theories of technical change, on systems theory, on innovation systems theory, on theories of industrial innovation and on an ever-present historical perspective. There are two main thrusts behind this work. The first is the realisation that there are national differences in economic development rates and more particularly in innovation rates and that there is a need to explain those differences. The second thrust addresses the need to explain the variation at firm level and how the behaviour of firms is related to its innovative performance. A general model, based on the chain-linked model of innovation, is developed as a conceptual framework to achieve the goal of explaining variation at a firm level. The explanation of the reciprocal interactions between the two main conceptual blocks, the firms and the environment, is the final goal of this study. The main research questions are: What is the main determinant of Portuguese indigenous industrial innovation? Is it the political/economic/cultural institutional environment? Or is it the strategy followed by the economic agents? What is the relative importance of each factor in the process of indigenous industrial innovation?